Ventriculoperitoneal shunt entry points in patients undergoing shunt placement: A single-center study - Younis Baregzai; Mohammed Maan Al-Salihi; Amro Al Hajali; Firas Hammadi; Ali Ayyad (World Neurosurgery: X, 2024)
Background: The ventriculoperitoneal (VP) shunt redirects cerebrospinal fluid flow, with the selection of entry points crucial for optimal outcomes. Anatomical landmarks and specific entry points, such as Kocher's, Frazier's, Keen's, and Dandy's points, have been utilized for shunt catheter placement. This study investigates the impact of various entry points on outcomes, particularly the necessity for revision procedures, in patients undergoing VP shunt placement. Methods: In this retrospective cohort study, we analyzed data from patients in our center's database, collected from October 2017 to October 2022. Participants were classified based on ventriculoperitoneal shunt entry points. The study followed STROBE guidelines. Continuous variables were presented as means with standard deviations (SD) and categorical variables as frequencies and percentages. Linear Model ANOVA and Pearson's Chi-squared tests were used for comparisons. Data analysis was conducted using Jamovi software. Results: Our study included 94 patients who underwent shunt procedures. The patients were categorized into four treatment groups: Dandy point (10), Frazier point (21), Keen point (43), and Kocher point (20). Conclusion: Our study found no significant differences in age, FOHR, and indication for shunt placement among catheter entry point subgroups. However, gender distribution, catheter length, and catheter tip location significantly varied. The proportion of patients requiring revision surgery varied among the groups, with the highest rate in the Dandy point group and the lowest in the Keen group; however, the difference among the entry groups was insignificant.